PENGARUH KEMITRAAN USAHA KOPERASI SUSU TERHADAP JUMLAH PENDAPATAN PETERNAK SAPI PERAH DI DESA GEGER KECAMATAN SENDANG KABUPATEN TULUNGAGUNG - Endra Hardiyanti; Dwi Susilowati; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2020)
A dairy cooperative business is a part of income that has a major impact on the economy of rural communities. In this study, there is a partnership between the Desa Tani Wilis unit and cooperative dairy farmers who are connected to improve the quality of milk so that milk can be further increased to be ready to be marketed to Nestle's milk factory, and increase the income of dairy farmers. The results showed that this partnership was quite successful because of the beneficial partnership for the breeders. The results showed that the initial capital, the number of cows, and the length of time they were members of the cooperative affected the income of dairy farmers. By taking 30 samples in Geger Village, Sendang District, Tulungagung Regency. The method used is SPSS and uses income analysis, multiple regression analysis, and statistical tests. The results of this study indicate that the variables of initial capital, number of cows, and length of time being members of the cooperative have a significant effect on income.